Planejamento e investimentos publicos no setor agropecuario baiano - Santos, Reginaldo Souza (2011)
Submitted by Estagiário SPT BMHS (spt@fgv.br) on 2011-09-09T17:58:32Z No. of bitstreams: 1 000029918.pdf: 4895833 bytes, checksum: 6b7390f7dfc356be09070f9c44c13638 (MD5) === Approved for entry into archive by Estagiário SPT BMHS (spt@fgv.br) on 2011-09-09T17:59:11Z (GMT) No. of bitstreams: 1 000029918.pdf: 4895833 bytes, checksum: 6b7390f7dfc356be09070f9c44c13638 (MD5) === Approved for entry into archive by Estagiário SPT BMHS (spt@fgv.br) on 2011-09-09T17:59:22Z (GMT) No. of bitstreams: 1 000029918.pdf: 4895833 bytes, checksum: 6b7390f7dfc356be09070f9c44c13638 (MD5) === Made available in DSpace on 2011-09-09T17:59:36Z (GMT). No. of bitstreams: 1 000029918.pdf: 4895833 bytes, checksum: 6b7390f7dfc356be09070f9c44c13638 (MD5) Previous issue date: 1983-09-09